Telling Tales, Print and the Extension of Media: Malay Media Studies Beginning with Abdullah Munsyi through Syed Shaykh Al-Hady and Mahathir Mohamad - Ahmad Murad Merican (Kajian Malaysia, 2006)
The representation and embodiment of Malay identity are certainly complex. How we know ourselves and how we have selected that knowledge determine the facts accumulated about us. What do the Malays make out of media? One assumption says that the Malays are averse to print and more attuned to orality and aurality. There is nevertheless also the category of baca, membaca and cerita which may not fit within the understanding of the European mind. Locating the categories of communication and media in the contexts of meaning, culture and thought may illustrate that the Malays do not share EuroAmerican presuppositions; at the same time, however, efforts to localise and indigenise the minda, concepts and practices only reattach them to the matrix of globalised modernity. Who represents what? Who represents media to Malay thought? What is being represented and at what levels?